2010
DOI: 10.1002/micr.20734
|View full text |Cite
|
Sign up to set email alerts
|

Free flap failure in an anticardiolipin antibody‐positive patient with neoplasm–A case report

Abstract: We present herein a case of massive arterial thrombosis of a free rectus abdominal musculocutaneous flap used for reconstructive surgery of gingival carcinoma that could not be rescued. A 54-year-old woman underwent the operation. She had experienced two miscarriages in her 20s, but medical history was otherwise uneventful. Intraoperatively, the anastomosed artery often showed massive arterial thrombosis, and the flaps had become necrotic after bilateral flaps were used. Laboratory findings, 7 days postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…[83][84][85][86][87][88][89][90][91][92][93] In a recent article by Wang et al examining 58 free flaps in patients with a variety of procoagulant states including factor V Leiden mutation, protein C deficiency, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, factor VIII elevation, anticardiolipin antibody syndrome, and essential thrombocytosis, a 20 percent rate of thrombosis and a 0 percent rate of salvage in flaps that had clotted postoperatively was reported (Level IV Evidence). 94 A retrospective series of 2260 free flaps concluded that elevated platelet count (>300,000/μl) and thrombophilia were risk factors for failure of a take-back, suggesting that platelet-derived blood coagulation pathways are important contributors to the flap failure pathologic condition (Level III Evidence).…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…[83][84][85][86][87][88][89][90][91][92][93] In a recent article by Wang et al examining 58 free flaps in patients with a variety of procoagulant states including factor V Leiden mutation, protein C deficiency, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, factor VIII elevation, anticardiolipin antibody syndrome, and essential thrombocytosis, a 20 percent rate of thrombosis and a 0 percent rate of salvage in flaps that had clotted postoperatively was reported (Level IV Evidence). 94 A retrospective series of 2260 free flaps concluded that elevated platelet count (>300,000/μl) and thrombophilia were risk factors for failure of a take-back, suggesting that platelet-derived blood coagulation pathways are important contributors to the flap failure pathologic condition (Level III Evidence).…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…Previous studies have reported undiagnosed hypercoagulability as a cause for unpredictable flap failures. [6][7][8][9][10][11] It was quite surprising to see that the incidence of hypercoagulability was not at all low, which goes to show that the state of hypercoagulation may be considered an underestimated condition. The percentages of newly diagnosed hypercoagulation shown in this study display the importance of questioning risk factors and testing accordingly for hypercoagulation in patients seeking microsurgical breast reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Asai et al state in their case report of a free flap failure due to undiagnosed thrombophilia that if the patient's state of hypercoagulation had been known prior to surgery, they would have selected a different approach for reconstruction. 9 Another reason to prefer techniques other than free tissue transfers in these patients is the ineffectiveness of standard microvascular salvage maneuvers if an anostomotic thrombosis were to occur. 7 The risk-benefit scale of the situation must be taken into consideration and the decision must be made according to the well-being of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid syndrome, which has been associated with certain cancers, has been associated with both venous and arterial thromboses. 29,32 On the other hand, MTHFR mutations impair folate metabolism and result in irreversibly increased plasma homocysteine levels. These are associated with mild increases in cardiovascular, DVT risk, and risk of pregnancy through an unclear mechanism, possibly related to reversibly increased platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%